2018
DOI: 10.1177/0954405418765307
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics and machining performance of TiAlN-, TiN- and AlCrN-coated tungsten carbide drills

Abstract: This article presents a comprehensive analysis of surface characteristics and drilling performance of uncoated and coated tungsten carbide drills. The single- and double-layer coatings of TiN, TiAlN and AlCrN were examined in terms of surface roughness, microhardness and crack resistance. In addition, drilling torque and thrust force were experimentally measured and compared to the developed models based on the drilling mechanics and drill geometries. Tool wear and hole surface roughness were also considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Similarly, the thrust force recorded using TiAlN drills was between 49.26 and 62.27% higher than that recorded using AlTiN/TiAlN tools. A previous study also reported that the cutting forces generated using TiN-coated drills were lower than those generated by TiAlN-coated drills [52]. It could be speculated that the AlTiN/TiAlN coating provided a better self-lubricating effect due to its multilayer coating structure, but this needs to be confirmed in a future study.…”
Section: Resultsmentioning
confidence: 81%
“…Similarly, the thrust force recorded using TiAlN drills was between 49.26 and 62.27% higher than that recorded using AlTiN/TiAlN tools. A previous study also reported that the cutting forces generated using TiN-coated drills were lower than those generated by TiAlN-coated drills [52]. It could be speculated that the AlTiN/TiAlN coating provided a better self-lubricating effect due to its multilayer coating structure, but this needs to be confirmed in a future study.…”
Section: Resultsmentioning
confidence: 81%
“…According to Bouzakis et al [31], the good performance of TiAlN than TiSiN was due to the weaker adhesion properties of TiSiN, despite the increased strength. Also, as discussed earlier, the co-efficient of friction of TiSiN is more than TiAlN [21], which increased the tool wear by increasing the tendency of sticking the materials from the workpiece on the tools [15]. Besides, the reason for the high BUE of the coated drills than the uncoated drill bits might be due to the low drilling parameters selected in this study.…”
Section: Post Drilling Tool Conditionsmentioning
confidence: 81%
“…Besides, the coefficient of friction of TiSiN is greater than that of TiAlN coated tools [21], and according to Prengel et al [37], the low coefficient of friction reduces the BUE. Hence, smaller values can be expected due to the lower cutting loads and less tool wear as a result of coatings' low friction coefficient [15]. Therefore, multi-spindle drilling increases productivity by drilling more than one hole and using uncoated drills would save manufacturing costs.…”
Section: Assessment Of Hole Quality In Terms Of Surface Roughness and Burrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional drilling process, large amount of chips were generated from the workpiece, which get adhered with the tool as well as the workpiece and then damage the surface quality of a finished hole. [1][2][3][4] The reliability of joint strength depends on the characteristics such as efficient screw thread strength and clamping heavy loads which are not obtained through this way of conventional procedure. Besides, fastening of sheet metals or thin-walled structures via conventional drilling method requires threaded inserts or welded nuts.…”
Section: Introductionmentioning
confidence: 99%